The Role of Targeted HIV Screening in the Emergency Department: A Scoping Review - Spagnolello, Ornella; Gallagher, Bernadette; Lone, Nazir; Ceccarelli, Giancarlo; D’Ettorre, Gabriella; Reed, Matthew J. (Current HIV Research, 2021)
Background: Human immunodeficiency virus (HIV) infection continues to expand worldwide, and a significant proportion of infection is still undiagnosed. Recent studies have addressed the impact and feasibility of ‘opt-out’ HIV screening in Emergency Departments (EDs) in urban settings at high HIV prevalence, whereas little is known about the yield of implementing ‘targeted’ HIV testing, especially in low-prevalence areas. Objective: The present study undertakes a scoping review of research carried out on the implementation of targeted HIV screening of adult in EDs to determine the impact, feasibility and acceptability of HIV testing in different HIV prevalence settings. Design: Online databases (EMBASE, MEDLINE) were used to identify papers published between 2000 to 2020. A three-concept search was employed with HIV (HIV, Human immunodeficiency virus infection, HIV infections), targeted testing (Target, screening or testing) and emergency medicine (Emergency Service, emergency ward, A, accident and emergency or Emergency Department) (28th February 2020). Only full-text articles written in English, French, Spanish or Italian and using impact and/or feasibility and/or acceptability of the program as primary or secondary outcomes were analysed. Results: The search provided 416 articles. Of these, 12 met inclusion criteria and were included in the final review. Most of the included studies were carried out in the United States (n=8; 67%) and in areas of high HIV prevalence (n=11; 92%). Three (20%) were randomized control studies. While the rate of newly diagnosed HIV cases varied widely (0.03-2.2%), likely due to methodological heterogeneity between studies, the linkage of new HIV diagnosis was often high (80-100%) and median CD4+ cell count was always greater than 200 cells per microliter. Targeted HIV screening was found to be cost-effective (out of 2 studies) and well accepted by participants (out 2 studies). Conclusions: Targeted HIV screening at the ED can be impactful, feasible and well accepted, but often requires extra funding and staff. Most previous work has focused on areas of high disease prevalence.
Keywords: public health